MEMBANGUN TEKNOLOGI BIDANG ILMU PENDIDIKAN DASAR UNTUK MENEMUKAN KARYA KREATIF DAN INOVATIV MELALUI PENELITIAN PRAKTIK KEBIJAKAN PENDIDIKAN SEKOLAH DASAR DALAM PERSPEKTIF HISTORIS - Erlina Yuliastuti; Dwi Agung Prasetiyo; Yugga Tri Surahman (STKIP Subang, 2025)
The development of technology in the 21st century has brought fundamental changes to the education system, particularly in primary education in Indonesia. Digital transformation requires the renewal of learning processes that not only focus on cognitive achievement but also on fostering students’ creativity and innovation. This article aims to examine the development of technology in the field of primary education in order to generate creative and innovative works through research on primary school education policy practices from a historical perspective. This study employs a qualitative approach using a literature review method, utilizing various sources such as books, academic journal articles, and relevant education policy documents. The results indicate that educational technology has undergone significant conceptual and practical development since the early 20th century to the present digital era, marked by a shift from simple visual media to the integration of digital- and multimedia-based learning systems. Primary education policies in the field of technology play a strategic role in directing the integration of technology into curricula and learning practices to improve educational quality. Furthermore, the application of technology in learning encourages creativity and innovation through the use of interactive media, e-learning, gamification, and the strengthening of digital literacy. Thus, the development of technology in primary education serves not only as a supporting tool for learning but also as an important instrument in shaping an adaptive, creative, and innovative educational ecosystem in accordance with the demands of the times and the needs of Indonesian students.